Radikalisme dalam Media Sosial sebagai Tantangan di Era Globalisasi - Jeanie Annissa; Ricky Widyananda Putra (Neolectura, 2021)
This research discusses the spread of radicalism through social media as a challenge in the era of globalization. Social media as a new communication platform in the era of globalization that provides a variety of information and easy access for radical movement groups to spread understanding and shape public opinion in society. The rise of radical content through social media can be a challenge for the state to create state unity and minimize conflicts between siblings. This study uses a qualitative method with a descriptive analytical approach and uses secondary data collection techniques. The results of this study indicate that social media can be a means for spreading radicalism content and influencing mindsets and values even though it is only through private spaces. In addition, to face the challenges of globalization that arise due to the wide influence of information, there must be optimization of the role of the state, such as efforts to implement a hybrid government model and implement social control in the community in contributing to maintaining community unity.